Creating a questionnaire to explore language teacher multilingual beliefs and practices - Osidak, Viktoriya; Natsiuk, Maryana; Vogt, Karin (East European Journal of Psycholinguistics, 2023)
Ukraine is a multilingual country whose language policy strives to promote language diversity. However, foreign language teaching is predominantly based on monolingual practice and languages are taught in isolation from one another in a foreign language classroom. These facts lead to realizing that language teachers should be trained in order to be able to promote their students’ multilingualism through employing their multilingual resources. Before the multilingual training or programme design, it is essential to evaluate teachers’ multilingual beliefs and teaching practices to make targeted and informed changes. The paper describes the evolution of the questionnaire to explore Ukrainian university language teachers’ beliefs about multilingualism and multilingual practices. For this purpose, a detailed insight into the phases and steps of the questionnaire development is presented. This comprises scrutiny of theory-based evidence to map the constituents of language teacher multilingualism, the description of how critical concepts for the study were identified and how relevant content for each part of the questionnaire was generated. In addition, the questionnaire’s verification process is described in detail, including item analysis carried out with Cronbach’s Alpha to verify the internal consistency of the items, participants’ feedback and expert’s opinion to explore content validity and participants’ feedback to check feasibility. The study invited 37 language teachers from different European and Ukrainian universities to complete the pilot questionnaire. The preliminary results of the pilot version are discussed, and a finalized version of the questionnaire is offered. In addition, this study adds to the knowledge of teachers’ current perspectives on practices in multilingual education. Funding Statement This study was funded by the Volkswagen Foundation Research Programme. Disclosure statement No potential conflict of interest was reported by the authors. * Corresponding author: Viktoriya Osidak, 0000-0001-7304-3026 viktoriya_osidak@ukr.net